(untitled) (International Journal of Engineering Management Science, 2023)
The objectives which the Father of the Nation “Gandhijee” had set for khadi work, by and large, continue to be relevant even now. Khadi continues to be the main source of employment for the spinners and weavers throughout this country because they could not get an alternate source of employment at their door-steps. In this paper, we investigate the performance of “KHADI” in economic growth and economic development of India from 2007 to 2014 in terms of production of khadi textile, sales of khadi textile, employment generated by khadi textile industry and earnings generated by khadi textile industry for the khadi workers. An explorative as well as descriptive research methodology is used to get the data related to these aspects. The correlation analysis shows a very strong relationship between the selected variables.